Identification and validation of viral antigens sharing sequence and structural homology with tumor-associated antigens (TAAs). Issue 5 (28th May 2021) - Ragone, Concetta; Manolio, Carmen; Cavalluzzo, Beatrice; Mauriello, Angela; Tornesello, Maria Lina; Buonaguro, Franco M; Castiglione, Filippo; Vitagliano, Luigi; Iaccarino, Emanuela; Ruvo, Menotti; Tagliamonte, Maria; Buonaguro, Luigi
Abstract : Background: The host's immune system develops in equilibrium with both cellular self-antigens and non-self-antigens derived from microorganisms which enter the body during lifetime. In addition, during the years, a tumor may arise presenting to the immune system an additional pool of non-self-antigens, namely tumor antigens (tumor-associated antigens, TAAs; tumor-specific antigens, TSAs). Methods: In the present study, we looked for homology between published TAAs and non-self-viral-derived epitopes. Bioinformatics analyses and ex vivo immunological validations have been performed. Results: Surprisingly, several of such homologies have been found. Moreover, structural similarities between paired TAAs and viral peptides as well as comparable patterns of contact with HLA and T cell receptor (TCR) α and β chains have been observed. Therefore, the two classes of non-self-antigens (viral antigens and tumor antigens) may converge, eliciting cross-reacting CD8 + T cell responses which possibly drive the fate of cancer development and progression. Conclusions: An established antiviral T cell memory may turn out to be an anticancer T cell memory, able to control the growth of a cancer developed during the lifetime if the expressed TAA is similar to the viral epitope. This may ultimately represent a relevant selective advantage for patients with cancer and may lead to a novel preventive anticancer vaccine strategy.